Patterns of jaw coarticulatory direction and linguomandibular coordination in VCV sequences - Recasens, Daniel (ZAS Papers in Linguistics, 2002)
Data on lingual movement, dorsopalatal contact and F2 frequency presented in previous papers of ours (Recasens, 2002; Recasens and Pallarès, 2001; Recasens, Pallarès and Fontdevila, 1997) suggest that the degree of articulatory constraint (DAC) model accounts to a large extent for the extent and direction of tongue dorsum coarticulation in VCV and CC sequences. A goal of this investigation is to verify the predictions of this model with respect to jaw V-to-V effects in VCV sequences using articulatory movement data collected with electromagnetic articulometry (EMA).